57 The role of the Clinical Nurse Specialist in neuro-oncology: Insights from a UK-wide review of adult brain tumour services (2020-2026) - Catharine James; Charlotte Robinson; Jillian Sokratous; Andrew Wright; Eloise Lines; Shona Floyd; Camille Goetz; Nicky Huskens (Neuro-Oncology, 2026)
Abstract Introduction Clinical Nurse Specialists (CNSs) are central to coordinating complex neuro-oncology pathways, yet national data on capacity and roles are lacking. We aimed to examine variation in CNS capacity, team structure, responsibilities, and training across UK adult brain tumour services. Method Data were collected from 25 NHS neuro-oncology centres (covering more than 90% of the UK population) in 2020–2026 through the Tessa Jowell Centre of Excellence programme, supplemented by national patient experience data from The Brain Tumour Charity. Quantitative data were analysed descriptively and qualitative findings thematically. Results CNS capacity varied more than fourfold, with 2.0–9.2 full-time equivalent (FTE) nurses per centre and 18–59 new glioma patients per CNS annually. Patient-reported access to a CNS ranged from 39% to 95% across centres. Team composition differed markedly: although all centres had Band 7 CNSs, only 8/25 (32%) reported Band 8 roles, and 5/25 (20%) had low-grade glioma-specific posts. Non-medical prescribing was unavailable in one-third of centres. Despite structural variation, CNSs consistently delivered core functions, including diagnostic communication, holistic needs assessments, CNS-led clinics, symptom management, and pathway coordination. Support worker roles increased from 2020 to 2026 (32% to 54% of centres), helping release CNS time, although distribution remained uneven. Access to funded training was limited (36% NHS-funded), with reliance on charitable and informal networks. Conclusions CNSs are the backbone of UK neuro-oncology services but are inconsistently resourced, with substantial variation in capacity, seniority, skill mix, and training. These differences likely contribute to geographical inequities in patient experience. The Tessa Jowell Brain Cancer Mission will work with partners to ensure national standardisation of CNS capacity benchmarks, role definitions, leadership structures, and protected professional development.